2015
DOI: 10.1073/pnas.1518090112
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of histone modifications in episomal HBV cccDNA uncovers an unusual chromatin organization amenable to epigenetic manipulation

Abstract: Chronic hepatitis B virus (HBV) infection affects 240 million people worldwide and is a major risk factor for liver failure and hepatocellular carcinoma. Current antiviral therapy inhibits cytoplasmic HBV genomic replication, but is not curative because it does not directly affect nuclear HBV closed circular DNA (cccDNA), the genomic form that templates viral transcription and sustains viral persistence. Novel approaches that directly target cccDNA regulation would therefore be highly desirable. cccDNA is asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
272
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(318 citation statements)
references
References 67 publications
20
272
1
2
Order By: Relevance
“…6A). This was consistent with a recent report that precore/pgRNA were the most prominent HBV RNA species in de novo-infected HepG2/NTCP cells (36). Therefore, the differences in HBsAg/ HBeAg ratio after sHBV and ccHBV infection of the two cell types were somewhat reflected at the transcription level.…”
Section: Overviewsupporting
confidence: 93%
See 1 more Smart Citation
“…6A). This was consistent with a recent report that precore/pgRNA were the most prominent HBV RNA species in de novo-infected HepG2/NTCP cells (36). Therefore, the differences in HBsAg/ HBeAg ratio after sHBV and ccHBV infection of the two cell types were somewhat reflected at the transcription level.…”
Section: Overviewsupporting
confidence: 93%
“…Whether NTCP distorts the ratio between the 3.5-kb RNA and 2.4-kb/2.1-kb RNAs following ccHBV infection (Fig. 6A) (36) through the same host (transcription) factors requires further investigation, but such transcriptional alteration could partly explain the distorted HBsAg/ HBeAg ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Using a genome-wide ChIP-seq method, they found that the majority of Jmjd3 target genes were not associated with detectable level of H3K27me341 suggesting an H3K27 demethylation-independent mechanism. Recently, several studies have reported low levels of H3K27me3 at HBV promoters in HBV infected HepaRG and NTCP-HepG2 cells, primary human hepatocytes, as well as HBV-infected liver tissue4243. We also found that in our system, the level of H3K27me3 at the HBV En II promoter was extremely low compared to the promoter of IGF2 gene, whose expression is under control of promoter histone H3K27 methylation (data not shown)44.…”
Section: Discussionsupporting
confidence: 62%
“…333- to 625-fold enrichment for capped RNAs [26]), it is still possible to have artificial peaks on cleavage hot-spots produced by massive amounts of site-specific cleavage events. Nevertheless, a recent study using covalently closed circular DNA (cccDNA) ChIP-Seq approach has shown two distinct peaks of active promoter marks (H3K4me3, H3K27ac, and H3K122ac) within the X gene body, especially prominent in HBV-infected primary human hepatocytes and HBV-positive liver tissues (40). The second histone modification peak located at the middle of the X gene might be associated with the new TSS detected here.…”
Section: Resultsmentioning
confidence: 99%